KOMPARASI PENERAPAN MODEL CONTEXTUAL TEACHINGLEARNING DAN MODEL INQUIRY TERBIMBING TERHADAP HASIL BELAJAR IPAS KELAS IV UPT SDN INPRES SALIMBONGAN - Rahman, Nur Isda Niar; Muslimin; Natriani Syam (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the comparison of student learning outcomes in Contextual Teaching Learning and Guided Inquiry learning in class IV UPT SDN Inpres Salimbongan. The approach used is quantitative with a quasi-experimental research type in the form of a pretest-posttest group design. The population is all students of UPT SD Inpres Salimbongan, while the sample is class IVA as an experimental class of the Contextual Teaching Learning model with a total of 19 students and class IVB as an experimental class of Guided Inquiry with a total of 19 students, the sampling technique used is purposive sampling technique. The research data were obtained by providing Pretest and Posttest questions. The data analysis technique is the Independent Sample T-test. The Guided Inquiry model is more effective in improving learning outcomes because it emphasizes exploration. Investigation, and active involvement of students, meanwhile, Contextual Teaching Learning is more effective in building conceptual understanding by connecting material with real experiences of students. Based on the results of the inferential statistical analysis, it shows Sig (2-tailed) = 0.000 <0.05, so H0 is rejected and H1 is accepted. The results of the study indicate that there is a significant difference between the learning outcomes of students who use the Contextual Teaching Learning model and the Guided Inquiry model. Thus, the conclusion of this study is that there is a difference in the learning outcomes of students using Contextual Teaching Learning and Guided Inquiry learning models in class IV UPT SDN Inpres Salimbongan.